MINAT PESERTA DALAM MENGIKUTI PENCAK SILAT PADA PERGURUAN PERSAUDARAAN SETIA HATI TERATE (PSHT) KOTA LUBUKLINGGAU - Jannatun Naim; Ani Fiani; Hengky Remora ($$8@@&&$%K, 2021)
The purpose of this research was to determine the effect of agility training on the dribbling ability of SSB YF-13 Lubuklinggau player. Is research was an experimental research with. One Group Pretest-posttest design. The population of this research was SSB YF-13 players, totaling 24 people. The sampling technique used was total sampling and the variables in this study were zig-zag run exercises. The analysis of data used t-test statistics. The instrument used in this research was a dribble test instrument. The mean result of the initial test, Dre-tests result was 26.67 and the post-test was 19.88. From the results of the difference test, the difference in dribble speed for the experimental group was 7.723, the t-count value was 15.081 with a table value of 0.171 with a significance of 0.00≥ 0.05. It can be concluded that the agilty training has affected to the dribbling agility SSB YF-13 Player at Lubuklinggau.